2016
DOI: 10.1186/s13048-016-0244-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of topoisomerases for prognosis and drug resistance in ovarian cancer

Abstract: BackgroudAs magicians of the DNA world, topoisomerases resolve all of the topological problems in relation to DNA during a variety of genetic processes. While the prognostic value of topoisomerase isoenzymes in epithelial ovarian carcinoma (EOC) is still elusive. In current study, we investigated the prognostic value of topoisomerase isoenzymes in the EOC patients. Kaplan Meier plotter (KM plotter) database were used to assess the relevance of individual topoisomerase isoenzyme mRNA expression to EOC patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 56 publications
(61 reference statements)
0
28
0
Order By: Relevance
“…46 It was also suggested recently that Top1 may be a biomarker for poor prognosis in grade III endothelial ovarian cancer patients. 47 Taken together, these results suggest that Top1 may be a promising target for therapeutic intervention in cancer.…”
Section: Topoisomerase I In Cancer: Rationale For Enzyme Inhibitionmentioning
confidence: 88%
See 3 more Smart Citations
“…46 It was also suggested recently that Top1 may be a biomarker for poor prognosis in grade III endothelial ovarian cancer patients. 47 Taken together, these results suggest that Top1 may be a promising target for therapeutic intervention in cancer.…”
Section: Topoisomerase I In Cancer: Rationale For Enzyme Inhibitionmentioning
confidence: 88%
“…Zhao et al found by reverse transcription polymerase chain reaction (RT‐PCR) that high levels of Top1 correlated with reduced disease‐free survival in breast cancer patients (not treated with Top1 poisons), while other studies have correlated high Top1 with reduced survival in postoperative nonsmall‐cell lung cancer patients and poor prognosis in ovarian cancer . It was also suggested recently that Top1 may be a biomarker for poor prognosis in grade III endothelial ovarian cancer patients . Taken together, these results suggest that Top1 may be a promising target for therapeutic intervention in cancer.…”
Section: Topoisomerase I In Cancer: Rationale For Enzyme Inhibitionmentioning
confidence: 98%
See 2 more Smart Citations
“…By using the genome sequencing and bioinformatics approaches, TCGA catalogues genetic mutations responsible for various cancers, and this provides a rich source for investigators to analyze the potential mechanism of cancer pathogenesis. The "Kaplan-Meier plotter" (KM plotter), established using the gene expression data and relapse free and overall survival information downloaded from TCGA, as well as The European Genome-phenome Archive (EGA) and Gene Expression Omnibus (GEO) [9]. KM plotter has been reported to analyze the prognostic value of a particular gene and potential drug targets in NSCLC and other cancers [10][11][12][13][14].…”
mentioning
confidence: 99%